Max Weber's Approach: Bureaucracy and Power Structure in Modern Educational Organizations - Ali , Muhammad (Journal of Industrial Engineering & Management Research, 2023)
This research uses Max Weber's theory to investigate the role of bureaucracy and power structures in modern educational organizations. The main focus of this research is to determine how Weber's ideas of power and bureaucracy can be applied to modern educational institutions. The research method involves analyzing the literature on the related subjects of Max Weber's theory, bureaucracy, and power structures in contemporary education systems. This literature review included books, scientific journals, and conference papers. To support the research findings, the data collected was analyzed qualitatively. The study shows that Weber's bureaucratic principles, such as rational rules, division of tasks and hierarchy, are still relevant in modern educational organizations. However, their influence may vary depending on several things, such as flexibility, innovation and participation. Weber's theories of authority and control help to understand how power functions in modern educational institutions. Overall, this study provides a better understanding of Weber's theories in understanding bureaucratic dynamics as well as power in educational institutions; this can help the improvement and development of modern education systems.